Facilitation of synaptic transmission and pain responses by CGRP in the amygdala of normal rats - Ji Guangchen; Li Zhen; Adwanikar Hita; Han Jeong S; Neugebauer Volker (SAGE Publishing, 2010)
Abstract Calcitonin gene-related peptide (CGRP) plays an important role in peripheral and central sensitization. CGRP also is a key molecule in the spino-parabrachial-amygdaloid pain pathway. Blockade of CGRP1 receptors in the spinal cord or in the amygdala has antinociceptive effects in different pain models. Here we studied the electrophysiological mechanisms of behavioral effects of CGRP in the amygdala in normal animals without tissue injury. Whole-cell patch-clamp recordings of neurons in the latero-capsular division of the central nucleus of the amygdala (CeLC) in rat brain slices showed that CGRP (100 nM) increased excitatory postsynaptic currents (EPSCs) at the parabrachio-amygdaloid (PB-CeLC) synapse, the exclusive source of CGRP in the amygdala. Consistent with a postsynaptic mechanism of action, CGRP increased amplitude, but not frequency, of miniature EPSCs and did not affect paired-pulse facilitation. CGRP also increased neuronal excitability. CGRP-induced synaptic facilitation was reversed by an NMDA receptor antagonist (AP5, 50 μM) or a PKA inhibitor (KT5720, 1 μM), but not by a PKC inhibitor (GF109203X, 1 μM). Stereotaxic administration of CGRP (10 μM, concentration in microdialysis probe) into the CeLC by microdialysis in awake rats increased audible and ultrasonic vocalizations and decreased hindlimb withdrawal thresholds. Behavioral effects of CGRP were largely blocked by KT5720 (100 μM) but not by GF109203X (100 μM). The results show that CGRP in the amygdala exacerbates nocifensive and affective behavioral responses in normal animals through PKA- and NMDA receptor-dependent postsynaptic facilitation. Thus, increased CGRP levels in the amygdala might trigger pain in the absence of tissue injury.